2010
DOI: 10.1007/s10100-010-0137-8
|View full text |Cite
|
Sign up to set email alerts
|

A tabu search tutorial based on a real-world scheduling problem

Abstract: We apply a tabu search method to a scheduling problem of a company producing cables for cars: the task is to determine on what machines and in which order the cable jobs should be produced in order to save production costs. First, the problem is modeled as a combinatorial optimization problem. We then employ a tabu search algorithm as an approach to solve the specific problem of the company, adapt various intensification as well as diversification strategies within the algorithm, and demonstrate how these diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Tabu tenure is a number of previous solutions to be stored. In static memory, the value of tabu tenure is fixed and remains fixed during the search, while in dynamic memory, the value of tabu tenure is not constant during the search [21]. In this research, the static memory is selected in the search process.…”
Section: The Proposed Algorithmmentioning
confidence: 99%
“…Tabu tenure is a number of previous solutions to be stored. In static memory, the value of tabu tenure is fixed and remains fixed during the search, while in dynamic memory, the value of tabu tenure is not constant during the search [21]. In this research, the static memory is selected in the search process.…”
Section: The Proposed Algorithmmentioning
confidence: 99%
“…James et al (2009) showed the advantages of applying strategic diversification within Tabu search (TS) model for the quadratic assignment problem by including many diversification and multi start TS variants [61]. Ulrike (2011) applied TS to Scheduling problem then with the help of intensification and diversification strategies demonstrates that the result achieved is quite better [115].…”
Section: Tabu Searchmentioning
confidence: 99%
“…Metaheuristic search methods include local search or neighborhood search algorithms, which are iterative procedures and start with an initial solution and browse through the search space, picking up better solutions on the way, which could give good, or eventually optimal, solutions (Schneider 2011). Therefore, this study considered the application of a genetic algorithm (GA), a simulated annealing (SA) and a heuristic algorithm to solve the considered problem with minimization of the makespan.…”
Section: The Proposed Solving Approach and Proceduresmentioning
confidence: 99%